2002
DOI: 10.1007/bf03032296
|View full text |Cite
|
Sign up to set email alerts
|

Temporary and permanent biventricular pacing via left ventricular epicardial leads implanted during primary cardiac surgery

Abstract: Temporary BVP during the short-term after cardiac surgery improved cardiac function and decreased mitral regurgitation in all 4 of our patients. Epicardial lead implantation may thus be a useful option during surgical treatment of patients with CHF and intraventricular conduction delay if long-term permanent BVP is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
4
10
0
Order By: Relevance
“…We found BiVP ineffective after primary coronary bypass or primary mitral surgery, consistent with previous studies [1628]. …”
Section: Commentsupporting
confidence: 92%
See 2 more Smart Citations
“…We found BiVP ineffective after primary coronary bypass or primary mitral surgery, consistent with previous studies [1628]. …”
Section: Commentsupporting
confidence: 92%
“…BiPACS [3,4,13,3234] and previous studies [1628] suggest that future pacing research should focus on aortic valve surgery and should distinguish benefits of rate acceleration from resynchronization. This may confirm whether the complexity of BiVP is justified, or whether accelerated heart rate alone is sufficient.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Correctly timing different chamber excitation, and restoration of the ventricular synchronized contraction and relaxation can improve cardiac performance. Anecdotally, we have been able to achieve a significant reduction of mitral regurgitation after initiation of BiV pacing, which has also been shown in other studies 14,15 . Additionally, this method has been anecdotally performed in patients with prolonged conduction and reduced systolic function in whom a postoperative permanent BiV pacemaker is planned.…”
supporting
confidence: 65%
“…These acute benefits of BiVP suggest its possible value as an adjunct to the treatment of LV or right ventricular (RV) dysfunction after cardiac surgery. Although its use for perioperative management has not been carefully evaluated, initial studies have shown the utility of temporary BiVP after surgery for acquired (19,56) and congenital (27,40,47) heart disease.…”
mentioning
confidence: 99%